Structural imbalance, income inequality and economic growth - Wang, X.; Zhou, Yixiao (ANU E Press, 2014)
A series of structural imbalances has persisted in the Chinese economy. The consumption rate has been declining for years and has been significantly lower than the international average, while the savings rate and the capital formation rate have been too high and continue to rise. Massive investment has caused the rapid expansion of production capacity, while consumption growth cannot keep up with the expansion of capital investment and production capacity, resulting in a sustained excess capacity. Without structural change, the Chinese economy will gradually lose momentum due to the deficiency of domestic demand.